Bare Interior Grey light: Iscenesættelse af blikket på det tomme rum - Christoffersen, Erik Exe (Peripeti, 2021)
In his article »Bare Interior Grey Light« Christoffersen discusses an attempt to orchestrate a division between the theatrical and the performative levels in Beckett’s Endgame (1958) by a special staging grip, which he names the vertical optic.